Modelagem dinâmica, identificação de parâmetros e controle de um veículo aéreo não tripulado do tipo quadricóptero - Silva, Monique Fernandes da (2015)
The Unmanned Aerial Vehicles (UAVs) have received increasing attention in recent years as a way to replace the expensive manned vehicles. At first, UAVs were used for military applications, and currently they are used in the research and development area, where control techniques for stability and airworthiness are the main objects of study. The full development of autonomous flight in all environments is still a challenge. In this regard, the general objective of this work is to control the propulsion system of a quadrotor UAV for indoor altitude control application. The quadrotor system developed in this work consists of frame, four propellers, flight controller, sensors, four brushless direct current motors (BLDC), electronic speed controller (ESC), battery, radio control transmitter, receiver and universal circuit battery eliminator (UBEC). The software used for the simulation of Proportional Integral Derivative (PID) control for motor speed and altitude control was Simulink®/MATLAB. For the control development, it was necessary to model the quadrotor system to obtain a mathematical representation that allows an analytical study consistent with the system behavior in practice. The mathematical modeling of the quadrotor was performed using the Euler-Lagrange formalism, because it has the same form in any system of generalized coordinates and it is more suitable for generalizations. Tests were done to ensure proper operation of each part of the system, and quadrotor experiments were performed to calculate the motor thrust factor and to identificate parameters of BLDC motors. From the parameters identified in the experiments, the transfer functions required in PID control simulation of BLDC motor speed and quadrotor altitude were obtained. The experiment relating to PID control of motor speed was performed and the obtained values were compared with the simulated ones. The simulations and tests showed expected responses compared to the results of studies reported in the literature. This work begins new researches on UAVs area at the Universidade Federal Rural do Semi-Árido (UFERSA)